Análise de performance em layouts para melhoria de fluxo e de indicadores na parte de montagem de uma indústria automotiva - Dierka, Gabriela (2022)
The automotive market is undergoing transformations at a global level, often demanding new and large investments in innovative and effective products and processes. For this, it is necessary to be able to produce new vehicle models concomitantly with products that have been in serial production for a longer time. One of the classic ways to obtain greater production capacity is through improving the layouts of manufacturing facilities. In this way, this work carried out a case study with the objective of studying the insertion of new parts for new vehicle models that will be produced soon in a layout of an existing picking area to feed the production line of vehicles that are in fabrication today, seeking to identify problems and apply some Lean Manufacturing concepts to improve their performance. To improve this layout, it was proposed to separate value-added activities from non-value-added activities and whether this can be advantageous for the industry in question. It was also found that in the current situation of this picking, the operating times of each operator are unbalanced, generating an idle time considered high in some jobs. With this, the operation times of each workstation, performance indicators RGU (General Plant Yield), DSTR (Design Standard Time Ratio) and pieces per m² of the current state were verified and a comparison was made with the expected results. Improvement proposals, and then, together with the estimated cost, analyze whether the improvement proposals obtained from this work will be implemented. It was seen that performing all these calculations, the new layout proposal is feasible and advantageous for the automaker, since all indicators have improved and it is financially viable.